2018
DOI: 10.2147/dddt.s163645
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Tongfu powder in acute pancreatitis patients with gastrointestinal dysfunction: a clinical trial

Abstract: ObjectiveTo evaluate the efficacy and safety of Tongfu powder for external application on Shénquè (the umbilicus, hereafter, Tongfu powder) versus mosapride in acute pancreatitis (AP) patients with gastrointestinal dysfunction.MethodsA total of 102 AP patients were diagnosed using the latest Atlanta Criterion and recruited at the Department of Infectious Disease, Beijing Friendship Hospital (Beijing, People’s Republic of China) from August 2014 to December 2016. Patients were randomized into the Tongfu powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Previous studies have demonstrated that ROS formation is closely linked to AP (Kim, 2008;Thareja, Bhardwaj, Sateesh, & Saraya, 2009). This decrease also determines the se- (Li, Zhang, Zhou, Zhang, & Li, 2017;Miao et al, 2018). This decrease also determines the se- (Li, Zhang, Zhou, Zhang, & Li, 2017;Miao et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have demonstrated that ROS formation is closely linked to AP (Kim, 2008;Thareja, Bhardwaj, Sateesh, & Saraya, 2009). This decrease also determines the se- (Li, Zhang, Zhou, Zhang, & Li, 2017;Miao et al, 2018). This decrease also determines the se- (Li, Zhang, Zhou, Zhang, & Li, 2017;Miao et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, the published guidelines for AP treatment in China stated that Traditional Chinese Medicine (TCM), which involves the use of single plants or formulas, can be used as a promising complementary therapy for AP. It has also been demonstrated by experimental and clinical studies that plants and formulations used in TCM are effective in the treatment of AP (Li, Zhang, Zhou, Zhang, & Li, 2017;Miao et al, 2018). In this study, the beneficial effects of MC on AP have been explored.…”
Section: Discussionmentioning
confidence: 96%
“…We included 102 studies with a total of 8830 patients (Figure 1). Eighty‐six studies (84%) were clinical trials 13–98 and 16 (14%) were observational studies 99–114 . Nine studies (7%) were only available in the form of a conference abstract; seven clinical trials and two observational studies 88–93,96,100,107 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight studies (65%) 38,53,59,61,68,72–75,78–82,87–91,93,97,98,106,107,109,110,112,114 reported patient‐centred outcomes including hospital LOS, mortality, surgical complications, infections, need for surgery and readmission rate.…”
Section: Resultsmentioning
confidence: 99%
“…Several prokinetic GI hormones, such as circulatory motilin and ghrelin, were reported to be decreased in AP 1,44,45 . Miao et al 46 treated AP patients with a special kind of traditional Chinese Medicine named Tongfu powder via umbilical compress therapy and reported improvement in GI dysmotility concurrent with an increase in motilin. However, motilin was not altered with the TEA treatment in the present study.…”
Section: Discussionmentioning
confidence: 99%